Graff's textbook of routine urinalysis and body fluids 2026-02-15T14:20:03+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Mundt, Lillian A.; Shanahan, Kristy (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)

(untitled)
Graff's Textbook of Urinalysis and Body Fluids is the best urinalysis reference for laboratory students and professionals. In its Second Edition, this practical book retains its full-color images and top-notch coverage of urinalysis principles while significantly updating the content, broadening the scope to include new material on body fluids, providing more information on safety and quality assurance, and adding textbook features such as objectives, case studies, and study questions